1985
DOI: 10.1128/jcm.22.6.1071-1072.1985
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of ortho respiratory syncytial virus enzyme-linked immunosorbent assay and HEp-2 cell culture

Abstract: Two hundred seventy nasopharyngeal aspirates were tested in duplicate with the Ortho Diagnostics, Inc. (Raritan, N.J.), respiratory syncytial virus antigen enzyme-linked immnunosorbent assay. The test was sensitive

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
12
0

Year Published

1987
1987
1990
1990

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(13 citation statements)
references
References 7 publications
1
12
0
Order By: Relevance
“…In other RSV studies 10 to 20% of the (5,11,12,15,37,44,46,49,52). The reported sensitivity of enzyme-linked immunosorbent assay and radioimmunoassays when compared with culture or immunofluorescence methods have ranged from 61 to 96% (1,7,8,10,12,14,16,18,28,29,35,37,39,44,48,49,53).…”
mentioning
confidence: 99%
“…In other RSV studies 10 to 20% of the (5,11,12,15,37,44,46,49,52). The reported sensitivity of enzyme-linked immunosorbent assay and radioimmunoassays when compared with culture or immunofluorescence methods have ranged from 61 to 96% (1,7,8,10,12,14,16,18,28,29,35,37,39,44,48,49,53).…”
mentioning
confidence: 99%
“…Immunofluorescence (IF) and enzyme-linked immunosorbent assay (ELISA) tests for the detection of respiratory viruses have been widely used [Bromberg et al, 1985;Chonmaitree et al, 1987;Hendry et al, 1982;Hornsleth and Friis, 1982;Kaul et al, 19781 and found to be useful diagnostic techniques [Grandien et al, 1985;Harmon and Pawlik, 19821, both affording speed and accuracy.…”
Section: Introductionmentioning
confidence: 99%
“…Confirmation of a viral etiology for respiratory infections is important, particularly as more antiviral therapy becomes available (11,13). The success of detection of a respiratory virus depends on many variables, including the site of collection and the type of specimen used (1,4,6,8,10,12,(14)(15)(16)(17)(18)20). The most commonly recommended respiratory specimens for viral isolation in children are nasal washes and nasopharyngeal aspirates (NPAs) (1,8,12,17,18,20).…”
mentioning
confidence: 99%
“…In the remaining 33 patients, the order of collection was not noted. NPA specimens were collected by suction of nasopharyngeal secretions from one nostril into mucous traps, as described previously (1,4,8). Secretions remaining in the catheter were washed off by suctioning 1 ml of viral transport medium (minimal essential medium containing 25 mM N-2-hydroxyethylpiperazine-N'-2-ethanesulfonic acid [HEPES; pH 7.4], 5.4 mM sodium bicarbonate, 10 ,ug of gentamicin per ml, and 0.6% fetal bovine serum) through the catheter.…”
mentioning
confidence: 99%
See 1 more Smart Citation